Propagation Characterization of Implantable Antenna At UWB Frequency - A Review - Abu, Maisarah; Mohamad, Najmiah Radiah; othman, adib; Mohd Aris, Nor Azlan; Subramaniam, indra devi; izahar, nurul hafiza (Universiti Teknologi Malaysia, 2015)
A technology of wireless body area network (WBAN) was invented in order to enhance the quality of healthcare management as well as to determine faster disease prevention. However, to obtain the real-time data of images and videos from inside the human body, an implantable device is required. Currently, the Medical Implant Communication System (MICS) is used, but, this system has limited data rate which is a narrow-band of 402 – 405 MHz. Thus, this study on Ultra Wideband (UWB) for implanted device is conducted as UWB offers a wide transmission bandwidth as well as high data rate. Knowledge of radio wave propagation behaviour inside human body is needed to perform the implantation. Past researches related to this topic are limited and those conducted focused only on the human torso. This paper aims to provide a better understanding on the characteristics of radio wave propagation inside the human body by using an implantable device at UWB frequency. It is also hoped that this study could be used as reference for future research on this subject.